Incidence Rates of Endophthalmitis after Various Pharmaceutical Intravitreal Injections - Sciulli, Harrison; Miller, Alexander; Miller, Chase; Miller, David G (Indonesian Vitreoretinal Society, 2023)
Introduction: The purpose of this study is to analyze incidence rates of endophthalmitis after intravitreal injection(s) of bevacizumab (BEVA), brolucizumab (BROL), aflibercept (AFL), ranibizumab (RAN), dexamethasone implant (DEXA), and triamcinolone acetonide (TRIA). Methods: In this retrospective cohort study data was collected from patients who received intravitreal injections from January 2020 through November 2021, of AFL, BEVA, BROL, DEXA, TRIA and RAN. Data collected includes patient identification number, injection dates, medication injected, and procedure codes. Endophthalmitis rates were compared amongst medications and total percentage tabulated. Result: From January 2020 through November 2021, 109,202 injections were administered. Of the 109,202 injections administered: 66,095 were aflibercept, 28,762 bevacizumab, 8,650 ranibizumab, 3,010 brolucizumab, 1,958 dexamethasone implant, and 95 triamcinolone acetonide. Thirty-nine (0.036%) endophthalmitis cases occurred. Of the 39 endophthalmitis cases, 22 of the cases occurred (0.033% of total aflibercept injections) after aflibercept injection(s), 5 (0.688% of total triamcinolone acetonide injections) after triamcinolone acetonide injection(s), 5 (0.03% of total bevacizumab injections) after bevacizumab injection(s), 3 (0.153% of total dexamethasone implants) after dexamethasone implantation(s), 2 (0.066% of total brolucizumab injections) after brolucizumab injection(s), 2 (0.023% of total ranibizumab injections) after ranibizumab injection(s).(Table 1) Using a student’s t-test, the rate of endophthalmitis for TRIA versus all other medications was statistically significant with a p-value of 0.00152. Conclusion: Results show an endophthalmitis incidence rate of 0.036% after intravitreal injection(s) administration. This review suggests triamcinolone acetonide (TRIA) yielded a significantly higher incidence rate of endophthalmitis as compared to the other medications.